Signaling, Learning and Screening Prior to Trial: Informational Implications of Preliminary Injunctions - Thomas D. Jeitschko; Byung-Cheol Kim (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2011)
The decision to request a preliminary injunction—a court order that bans a party from certain actions until their lawfulness are ascertained in a final court ruling at trial—is an important litigation instrument in many areas of the law including antitrust, copyright, patents, trademarks, employment and labor relations as well as contracts. The process of filing for a preliminary injunction and the court's ruling on such a request generates information that can affect possible settlement decisions. We consider these implications when there is uncertainty about both the plaintiff's damages as well as the merits of case in the eyes of the court. Both plaintiff and defendant revise their beliefs about the case strength in dispute once they observe the court's ruling on preliminary injunctive relief. We study how such learning affects the likelihood of settlement. A precursor to this analysis is the study of the strategic role of preliminary injunctions as a means to signal the plaintiff's willingness to settle.
Keywords: D8; K12; K21; K41; J53; L4; 330; preliminary injunction; learning; signaling; screening; litigation; pre-trial motion; settlement